Penguatan Kompetensi Guru MGMP Geografi Kota Ambon dalam Pengembangan Bahan Ajar yang Efektif dan Inovatif - Sihasale, Daniel Anthoni; Salakory, Melianus; Pinoa, Wiclif Sephnath (Jurnal Pengabdian Arumbai, 2025)
Improving the competence of geography teachers in island regions faces challenges related to limited access, resources, and digital adaptation. This community engagement program aimed to enhance the capacity of the Geography Teachers’ Working Group (MGMP) in Ambon City in developing effective and innovative teaching materials based on local contexts. Activities included participatory workshops, digital learning material development, and continuous mentoring both offline and online. Results indicate a significant improvement in teachers’ ability to design, implement, and evaluate contextual learning materials. Over 80% of participants effectively utilized digital media and produced interactive products relevant to Ambon’s environment. This program highlights the effectiveness of collaborative and participatory approaches in strengthening teacher competence while fostering a sustainable professional network. The model offers a replicable reference for teacher empowerment in other regions through educational policy support and university collaboration